BIOCULTURAL CONSERVATION AND PROPAGATION OF NATIVE FRUIT TREES: THE NURSERY AS A GERMPLASM BANK AND EDUCATIONAL SPACE IN THE UPPER SOLIMÕES, AMAZON - Quitério, Talissa da Conceição; Moraes, Railma Pereira; Batista, Marxer Antonio Colares; Moraes, Joelson Vargas; Lima, Joelson da Silva; Leite, Valderice Mendes (Seven Editora, 2026)
This work aims to report the contribution of the seedling nursery to scientific research and environmental education in the Alto Solimões region of Amazonas. Seedling production is an essential tool for the conservation of floristic diversity in the Amazon. In this context, the Study Group in Environmental and Agricultural Sciences in the Amazon – GECAAM of the IFAM Tabatinga campus, develops research projects with the aim of highlighting and valuing endemic species of the Alto Solimões microregion. To this end, the group obtains resources from the Amazonas State Research Support Foundation – FAPEAM. Activities began in 2019 with the acquisition of materials for the construction of the nursery, such as: luminet, shade cloth, raffia, wires and wood. However, it was only in 2021 that experiments in the seedling nursery began, as well as practical classes, visits from institutions and the community. Twenty-three fruit species collected in municipalities of the Alto Solimões region were researched. At the end of the experiment, the seedlings are planted in environmental education initiatives developed by IFAM, donated to public and private institutions in the microregion, and to the general population. Since the project began in 2021, seedlings have already been distributed to five municipalities, notably to indigenous communities in the Javari Valley. It is concluded that the nursery transcends the simple production of seedlings, consolidating itself as a strategic instrument for food sovereignty, the conservation of biocultural heritage, and the formation of an ecologically critical citizenry.